Evaluation of Fermentation Using Ma-11 on The Nutrirional Content of Palm Leaves - Prasetyo, Ardina Nur; Sukaryani, Sri; Yakin, Engkus Ainul (Jurnal Biologi Tropis, 2024)
This study aims to determine the effect of fermentation of oil palm leaf content using MA-11 on dry matter (BK), crude protein (PK) and crude fibre (SK) content. This study uses a comprehensive randomized design (RAL) The pattern was in line with the treatment as many as four treatments and each treatment was repeated three times. T0 : 250 grams of palm oil leaves + 6cc MA-11 with an incubation period of 0 days, T1 : 250 grams of palm oil leaves + 6cc MA-11 with an incubation period of 3 days, T2: 250 grams of oil palm leaves + 6cc ma-11 with an incubation period of 6 days. T3 : 250 grams of palm oil leaf +6cc ma-11 with an incubation period of 9 days. Observed variable dry matter , crude protein, crude fibre.  The results of the study showed that the average value of BK was obtained T0: 86.86%, T1: 87.76%, T2: 88.93% and T3: 90.06%, Tilapia PK was obtained T0: 5.34%, T1: 6.04%, T2 6.01% and T3 12.09% The average value of SK was obtained T0: 23.12%, T1: 21.51%, T2: 20.30% and T3: 18.27%.The conclusion from this study is that the fermentation period of 0 to 9 days using ma-11 with a dose of 6cc has a very real effect on the dry matter content and crude protein content and is able to reduce the crude fiber content.